Pengaruh Salat Terhadap Etos Kerja Karyawan BTM Wiradesa - Rosanti, Cholisa; Sulaiman, Muh Andi; Setianto, Gigih; Fuad, Asfal (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
In the world of Islamic banking, employees who have precision, order and discipline in work are needed. One of the supporting factors in the effectiveness of working is the habit of prayer by each individual, in various books it is explained that there are many benefits of prayer. In addition to having religious value, it turns out that prayer is also able to influence character and positive attitudes. Prayer is also able to improve work ethic if carried out correctly. By always performing prayers, it will affect a person's work ethic. Therefore, the author wants to research how the influence of prayer on the work ethic of BTM Wiradesa employees. This research is a type of qualitative descriptive research. Data collection through observation, interviews and documentation studies. Then the data is analyzed through data reduction, data presentation and conclusions. The results of this study show that prayer is able to influence the work ethic of BTM Wiradesa employees, it turns out that in addition to having worship values, prayer is also able to foster positive attitudes at work such as increasing concentration, managing stress, increasing productivity, maintaining work spirit, being able to foster an attitude of cooperation, discipline, consistency and being able to foster the value of honesty.